Efek Limpahan Pertumbuhan Antar-Kabupaten/Kota di Provinsi Jawa Timur Tahun 2001–2013 - Wibisono, Pristiawan; Kuncoro, Mudrajad (Jurnal Ekonomi dan Pembangunan Indonesia, 2015)
This study aims to identify the typology of districts/municipalities in East Java Province, and analyze the growth spillover effects among districts/municipalities. This study was conducted using analysis tools such as Klaassen Typology, identification of growth pole based on the definition proposed by Richardson, the calculation of growth spillover effects and detection of spatial autocorrelation with local indexes Moran and Local Indicators of spatial Association (LISA). The results from this study is that advanced and fast-growing districts/municipalities from 2001 until 2013 concentrated in the central region of East Java Province. Consistency as advanced and fast-growing region is an indicator of growth poles, shown by Surabaya.